The Analysis of Students' Mathematical Critical Thinking Skills Solving HOTS-Based Problems - Putri, Dini Palupi; Cardoso, Luís Miguel Oliveira de Barros; Rahmadeni, Fevi; Wahyuni, Putri; Gusmuliana, Paidi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2025)
Abstracts The rapid development of technology in the digital era demands the readiness of students to compete and face various problems that arise. This requires critical thinking skills in formulating problems, finding solutions, and determining the resolution path. Critical thinking skills are needed in the 21st century, where information flows rapidly through digital technology. Critical thinking skills are needed to analyze information that benefits individual students. Innovation in the learning process to develop critical thinking skills involves familiarizing students with problem-based mathematical problems to hone critical thinking skills. HOTS questions are questions that stimulate critical thinking skills. This study will show students' critical thinking skills based on their initial abilities. The type of research used is descriptive quantitative. The instruments used are standard HOTS questions. Samples were taken from representatives of high, medium, and low initial ability students. Data analysis is carried out on student answer sheets. The results showed several critical thinking characteristics of students at every level of initial ability. Students with high initial abilities have maximized critical thinking skills based on indicators. Students with early, medium, and low abilities still do not master all indicators of critical thinking skills. Students must be trained by solving problems using HOTS questions to maximize critical thinking skills. HOTS-based problem-solving exercises are carried out regularly in lectures